2019
DOI: 10.3390/ijms20246231
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Abnormalities in Systemic Lupus Erythematosus and Lupus Nephritis—Role in Pathogenesis and Effect of Immunosuppressive Treatments

Abstract: Abnormalities in B cells play pivotal roles in the pathogenesis of systemic lupus erythematosus (SLE) and lupus nephritis (LN). Breach in central and peripheral tolerance mechanisms generates autoreactive B cells which contribute to the pathogenesis of SLE and LN. Dysregulation of B cell transcription factors, cytokines and B cell–T cell interaction can result in aberrant B cell maturation and autoantibody production. These immunological abnormalities also lead to perturbations in circulating and infiltrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 144 publications
(175 reference statements)
1
84
0
8
Order By: Relevance
“…Parallel to this, a decline in CD8 + T cells and a higher proportion of naïve CD4 + and CD8 + T cells have been observed ( 25 ). This finding is of special importance as it shows the direct impact of calorie restriction on B-cell and T-cell compartments, key immunocompetent cell compartments involved directly in SLE pathogenesis ( 26 , 27 ). In another SLE-prone mouse model, when a 40% calorie-restricted diet was provided, B:T cell and CD4 + :CD8 + T-cell ratios were significantly lowered compared with the control group ( 28 ).…”
Section: Macronutrientsmentioning
confidence: 92%
“…Parallel to this, a decline in CD8 + T cells and a higher proportion of naïve CD4 + and CD8 + T cells have been observed ( 25 ). This finding is of special importance as it shows the direct impact of calorie restriction on B-cell and T-cell compartments, key immunocompetent cell compartments involved directly in SLE pathogenesis ( 26 , 27 ). In another SLE-prone mouse model, when a 40% calorie-restricted diet was provided, B:T cell and CD4 + :CD8 + T-cell ratios were significantly lowered compared with the control group ( 28 ).…”
Section: Macronutrientsmentioning
confidence: 92%
“…The regulation of TF expression through the intracellular signal transduction pathways activated by T FH -cell-provided CD40L, IL-21 and IL-4 is essential for the GC response and B cell differentiation. The ability to monitor both this signaling and transcriptional regulation is necessary to enable fundamental research on wanted B cell responses against pathogens and unwanted B cell responses, as observed in autoimmune diseases [37][38][39] or during allo-antibody formation after blood transfusion [40]. Additionally, transcriptional dysregulation and overactivated signaling pathways can lead to B cell malignancies [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…B cells are central to the pathogenesis of SLE. Dysregulation of transcription factors and cytokines in B cells and interaction between B-T cells can lead to abnormal maturation of B cells and the production of autoantibodies ( 4 , 5 ). Targeted blocking of B-cell-related cytokines has an obvious effect on down-regulating the overly strong immune response.…”
Section: Targeting B Cellsmentioning
confidence: 99%